Glaciolacustrine Sedimentation During Advance and Retreat of the Cordilleran Ice Sheet in Central British Colombia - Eyles, Nicholas; Clague, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTThick (400+ m) and well exposed sediment fills in the Fraser and Chilcotin river valleys of central British Columbia record contrasting glaciolacustrine environments of at least two glaciations. The oldest glaciolacustrine sequence comprises deformed gravel, sand, mud, and diamict fades deposited, in part, on stagnant ice trapped in deep narrow valleys at the end of the penultimate glaciation (Early Wisconsinan or older). Younger glaciolacustrine sequences date from the advance and retreat phases of the Late Wisconsinan Fraser Glaciation {ca. 25-10 ka) and infill a Middle Wisconsinan drainage system cut across older sediments. The Late Wisconsinan advance sequence is dominated by diamict (debris-flow) fades that pass upward into silts. The diamict fades consist largely of reworked older Pleistocene drift and poorly lithified Cretaceous and Tertiary sediments. They record the focusing of large volumes of sediment into one or more glacial lakes occupying deep narrow troughs. Weakly bedded silts in the upper part of the sequence may have been deposited when the lake(s) deepened as glaciers continued to advance and thicken over the study area. It is possible that some advance glaciolacustrine sediments accumulated in subglacial water bodies. Late Wisconsinan deglacial lake sediments form a relatively thin, discontinuous capping in the area and conform to classical notions of gladolacustrine sedimentation involving a seasonal or 'varved' regime. In contrast, no seasonal pattern of sedimentation can be identified in older sequences where the overriding influence on deposition has been the presence of steep subaqueous slopes, buried ice masses, and high sediment fluxes; these, in combination, caused near-continuous downslope movement and resedimentation.